Women's decision-making and uptake of services to prevent mother-to-child HIV transmission in Zambia. Issue 4 (3rd April 2018) - Ford, Catherine; Chibwesha, Carla J.; Winston, Jennifer; Jacobs, Choolwe; Lubeya, Mwansa Ketty; Musonda, Patrick; Stringer, Jeffrey S. A.; Chi, Benjamin H.
ABSTRACT: Women's empowerment is associated with engagement in some areas of healthcare, but its role in prevention of mother-to-child HIV transmission (PMTCT) services has not been previously considered. In this secondary analysis, we investigated the association of women's decision-making and uptake of health services for PMTCT. Using data from population-based household surveys, we included women who reported delivery in the 2-year period prior to the survey and were HIV-infected. We measured a woman's self-reported role in decision-making in her own healthcare, making of large purchases, schooling of children, and healthcare for children. For each domain, respondents were categorized as having an "active" or "no active" role. We investigated associations between decision-making and specific steps along the PMTCT cascade: uptake of maternal antiretroviral drugs, uptake of infant HIV prophylaxis, and infant HIV testing. We calculated unadjusted and adjusted odds ratios via logistic regression. From March to December 2011, 344 HIV-infected mothers were surveyed and 276 completed the relevant survey questions. Of these, 190 (69%) took antiretroviral drugs during pregnancy; 175 (64%) of their HIV-exposed infants received antiretroviral prophylaxis; and 160 (58%) had their infant tested for HIV. There was no association between decision-making and maternal or infant antiretroviral drug use. We observed a significant association between decision-making and infant HIV testing in univariate analyses (OR 1.56–1.85; p  < 0.05); however, odds ratios for the decision-making indicators were no longer statistically significant predictors of infant HIV testing in multivariate analyses. In conclusion, women who reported an active role in decision-making trended toward a higher likelihood of uptake of infant testing in the PMTCT cascade. Larger studies are needed to evaluate the impact of empowerment initiatives on the PMTCT service utilization overall and infant testing in particular.